The Effectiveness Of Developing Self-Potential And Upgrading The Digitalization Of Msmes In The Implications Of Entrepreneurial Orientation - Hilda Sasqiyah Salsabila; Vanny Rahayu Fitriyani; Juhandina Ningsih; Anna Suzana (Publikasi Indonesia, 2024)
This study aims to evaluate the effectiveness of developing self-potential in MSMEs and the impact of increasing digitalization on entrepreneurial orientation. This study applies a quantitative descriptive approach by utilizing questionnaires as a tool to collect information with the Structural Equations Modeling Partial Least Square (SEM-PLS) data analysis method, using SMART PLS 4 software. From the tests that have been carried out, an R square value of 0.230 is obtained, which shows that the effectiveness of developing the potential and upgrading of MSME digitalization affects the entrepreneurial orientation. It was concluded that the development of self-potential and the increase in digitalization simultaneously affect the entrepreneurial orientation of MSME actors in Trusmi Kulon Village